Association between gp120 envelope V1V2 and V4V5 variable loop profiles in a defined HIV-1 transmission cluster. (19th June 2015) - Pollakis, Georgios; Baan, Elly; van Werkhoven, Maaike B.; Berkhout, Ben; Bakker, Margreet; Jurriaans, Suzanne; Paxton, William A.
Abstract : Objective: Variations in the HIV-1 gp120 Env variable loop sequences correlate with virus phenotypes associated with transmission and/or disease progression. We aimed to identify whether signature sequences could be identified in the gp120 Env between acute infection and chronic infection viruses obtained from a group of individuals infected with closely related viruses. Methods: To analyse acute infection versus chronic infection viruses, we studied a transmission cluster of 11 individuals, in which six presented during acute infection and five during chronic infection. Multiple HIV-1 gp120 Env clones were sequenced from each patient with predicted amino acid sequences compared between the groups. Results: Cluster analysis of V1V5 Env sequences ( n  = 215) identified that acute infection viruses had lower potential N-linked glycosylation site (PNGS) densities than viruses from chronic infection, with a higher amino acid length/PNGS ratio. We found a negative correlation between the V1V2 and V4V5 regions for both amino acid length (Pearson P  < 0.01) and PNGS numbers (Pearson P  < 0.01) during HIV-1 transmission. This association was lost following seroconversion. These findings were confirmed by analysing sequences from the Los Alamos database that were selected and grouped according to timing of transmission. This included acute infection sequences collected 0–10 days ( n  = 400) and chronic infection sequences 0.5–3 years postseroconversion ( n  = 394). Conclusion: Our observations are consistent with a structural association between the V1V2 and V4V5 gp120 regions that is lost following viral transmission. These structural considerations should be taken into consideration when devising HIV-1 immunogens aimed at inducing protective antibody responses targeting transmitted viruses.